2021
DOI: 10.3390/ijms22042180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Short-Term UV-B Radiation Intensities on Metabolic Characteristics of Porphyra haitanensis

Abstract: The effects of ultraviolet (UV) radiation, particularly UV-B on algae, have become an important issue as human-caused depletion of the protecting ozone layer has been reported. In this study, the effects of different short-term UV-B radiation on the growth, physiology, and metabolism of Porphyra haitanensis were examined. The growth of P. haitanensis decreased, and the bleaching phenomenon occurred in the thalli. The contents of total amino acids, soluble sugar, total protein, and mycosporine-like amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 72 publications
2
10
0
Order By: Relevance
“…Kusano et al [22] also demonstrated that carbon flux was dominant towards the shikimate pathway at the transcriptional level of the genes. Enhanced accumulation of secondary metabolites including lignin and flavonoids was proven as an early response against UVB stress [31][32][33][34][35] and was also observed in some plant species: rye [36], grapes [37], and cistus [38]. Our study carefully affords the probability that lignin and flavonoids feature both defensive and adaptive responses in an excessive UVB environment in terms of the increasing patterns in both younger (day 1) and older (day 5) stages and shows some accordance with previous observations.…”
Section: Lignin and Flavonoid Pathways Against Uvb Irradiationsupporting
confidence: 88%
“…Kusano et al [22] also demonstrated that carbon flux was dominant towards the shikimate pathway at the transcriptional level of the genes. Enhanced accumulation of secondary metabolites including lignin and flavonoids was proven as an early response against UVB stress [31][32][33][34][35] and was also observed in some plant species: rye [36], grapes [37], and cistus [38]. Our study carefully affords the probability that lignin and flavonoids feature both defensive and adaptive responses in an excessive UVB environment in terms of the increasing patterns in both younger (day 1) and older (day 5) stages and shows some accordance with previous observations.…”
Section: Lignin and Flavonoid Pathways Against Uvb Irradiationsupporting
confidence: 88%
“…Additionally, mycosporine-like amino acid (MAA) proteins unique to Porphyra increase throughout the harvest period and mitigate the effects of UV radiation and oxidative stress, promoting PSII D1 protein synthesis [ 42 ]. Previous research on Porphyra haitanensis reported that UV irradiation significantly increased the proline (Pro), serine (Ser), histidine (His), and alanine (Ala) content which, in turn, could offset stress-related cell damage, remove ROS, protect membrane integrity, enhance metabolic pathways, and increase the total sugar content [ 43 , 44 ]. These findings were consistent with our results (data not published).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of soluble sugar content and the enrichment of “starch and sucrose metabolism” pathway were also reported in rice under gamma rays, cosmic rays, and carbon-ion beams treatments ( Hwang et al, 2014 ), which is consistent with our result. The contents of soluble sugar, such as sucrose and D -glucose-6-phosphate, were increased in Porphyra haitanensis under UV-B exposure ( Fu et al, 2021 ). Combined with these studies, we suggested that the accumulation of soluble sugar and the activation of ROS scavenging processes might be the important processes for plants in response to IR irradiation.…”
Section: Discussionmentioning
confidence: 99%